CRYSTALLINE INCLUSIONS AND C ISOTOPE RATIOS IN DIAMONDS FROM THE SNAP LAKE/KING LAKE KIMBERLITE DYKE SYSTEM: EVIDENCE OF ULTRADEEP AND ENRICHED LITHOSPHERIC MANTLE - Pokhilenko N.P.; Sobolev N.V.; Reutsky V.N.; Hall A.E.; Taylor L.A. (My University, 2004)
U-type paragenesis inclusions predominate (94.7%) among the crystalline inclusion suite of 115 diamonds (−4+2 mm) obtained from the recently discovered Snap Lake/King Lake (SKL) kimberlite dyke system, Southern Slave, Canada. The most common inclusions are olivine (90) and enstatite (22). Sulfide, Cr-pyrope, chromite and Cr-diopside inclusion are less abundant (15, 10, 5 and 1, respectively). Results of the inclusion composition study demonstrate the following. (a) The relatively enriched character of the mantle parent rocks of the U-type diamonds. The average Mg# of olivine inclusions is 92.1, and of enstatite inclusions average 93.3. CaO content in Cr-pyrope inclusions is relatively high (3.73–5.75 wt.%). (b) Four of ten U-type Cr-rich pyrope inclusions contain a majoritic component up to 16.8 mol.% which requires pressures of ∼110 kbar. Carbon isotopes compositions for 34 diamonds with U-type inclusions have a δ13C range from −3.2‰ to −9‰ with a strong peak around −3.5‰. This is much heavier than the ratios of U-type diamonds from Siberia and South Africa (∼4.5‰). Diamonds with olivine inclusions can be divided into two groups based on their δ13C values as well as the Mg# and Ni/Fe ratio in the olivines. Most show a narrow range of δ13C values from −3.2‰ to −4.8‰ (average −3.72‰) and have olivine inclusions with Mg# less than 92.3 and relatively high Fe/Ni ratios. A second group is characterized by a much wider variation of C isotope composition (δ13C varies from −3.8‰ to −9.0‰, average −5.97‰), and the olivine inclusions having a higher Mg# (up to 93.6) and relatively low Fe/Ni ratios. This difference in the C isotope composition may have several explanations: (a) peculiarities of asthenosphere degassing coupled with an abnormal thickness of lithosphere; (b) the abnormal thickness and enriched character of lithospheric mantle; (c) involvement of subducted C of crustal origin in the processes of the diamond formation. The presence of subcalcic Cr-rich majorite (up to 17 mol.%) pyropes of low-Ca harzburgite paragenesis among the crystalline inclusion suite of SKL diamonds is strong evidence for the existence of diamondiferous depleted peridotite in lithospheric mantle at depth near 300 km beneath Southern Slave area and is postulated to be one of the main reasons for the much heavier C isotope composition of SKL U-type diamonds in comparison with those from Siberian and South African kimberlites.
Keywords: Crystalline inclusions; Carbon isotopes; Diamonds; Lithospheric mantle; Slave Craton